Elements of the Design and Implementation of Interventions to Prevent Violence against Women and Girls Associated with Success: Reflections from the What Works to Prevent Violence against Women and Girls? Global Programme - Rachel Jewkes (MDPI AG, 2021)
Intimate partner violence (IPV) has a large and sustained impact on women’s mental health, and so effective prevention is critical. A review of 96 rigorous evaluations of interventions for their impact on violence against women and girls (mostly IPV) found that several intervention approaches were effective. However, not every evaluation of a ‘successful approach’ showed success in reducing IPV. In order to understand what else impacts success, we analysed practitioners’ accounts and documentation of the design and implementation of seventeen interventions evaluated as part of What Works to Prevent Violence against Women and Girls (VAWG). Six features were identified as characteristics of all successful interventions: a rigorously planned intervention with a robust theory of change (ToC), attuned to the local context; addressing multiple drivers of VAWG; support for survivors; working with women and men; implementing at optimal intensity and having sufficient, well-selected, trained and supported staff and volunteers. Four features were necessary for success when relevant for the intervention approach: gender and social empowerment group activities and promoting positive interpersonal relations; participatory learning methods, emphasising empowerment, critical reflection and communication skills; carefully designed user-friendly manuals systematically followed; and when working with children, having an age-appropriate design with time for learning and an engaging pedagogy. This analysis provides the IPV prevention field with critical information for enhancing the impact of group- and community-based interventions in IPV prevention and through this strengthening women’s mental health.